Spirituality and Quality of Life in Limb Amputees - Peirano, Amanda H.; Franz, Randall W. (International Journal of Angiology, 2012)
Limb amputation is a life-changing event that signifies long-term physical, social, psychological, and environmental change. Spiritual well-being in patients plays a significant role in coping and may affect outcomes of patients with limb loss. The objective of this study was to describe the role of spirituality in individuals with limb amputation and to determine whether spirituality is related to the quality of life (QOL) in this sample. Study participants were recruited through prosthetists, physicians, amputee support groups, the Amputee Coalition of America, and amputee listserv discussion groups in the United States and Canada. Participants completed questionnaires containing measures of satisfaction with life, general health, mobility, and social integration. A quantitative descriptive research design was used to examine the relationships between existential spirituality (belief that one's life is meaningful or has purpose) and religious spirituality and QOL among individuals with limb amputation. A prospective study of 108 patients with a history of limb amputation was performed. The study population consisted of 66.3% males and 33.7% females. Most patients were Caucasian (96.2%). Of the 108 participants, 86 (79.6%) were 41 years of age or older with a mean of 18 years since amputation. The most frequent cause of amputation was trauma (55.6%) and the most common location of amputation was below-the-knee (49.1%). Existential spirituality, female gender, and age above 50 years related to higher QOL in patients with a history of limb amputation. The findings of this research confirmed that amputees use spirituality to cope with limb amputation. Existential spirituality was a significant predictor of satisfaction with life, general health, and social integration.
Keywords: quality of life; spirituality; well-being; coping; spirituality; limb amputation